The Roots of The Thermodynamic Laws - Mitrovic, Jovan (European Journal of Applied Sciences, 2024)
Historians of thermodynamics usually consider the Sadi Carnot’s memoir, appeared in 1824, as the origin of modern thermodynamics. A closer inspection of published works tells us another story. More than five decades prior to Carnot’s publication the Scottish instrument’s maker, whose name was James Watt, issued his ideas on thermodynamics. Today Watt is well known as originator of various ideas, particularly for his perfection of the steam engine. However, he is almost unknown as a scientist of thermodynamics. The present paper illustrates some of Watt’s original thermodynamic ideas which he obtained from the hidden principles of the steam engine. In around 1769 he recognized and formulated the foundations of modern thermodynamics. He illustrated the working principle of the steam engine by using the 1st and the 2nd law of thermodynamics which were absolutely unknown at that time. Despite these facts, the name of James Watt is banished from the history of thermodynamics. The Watt’s understanding and presentation of these laws are the pivotal subject of the present work.